Modified polypropylene material for battery housings, microcapsules used and method of preparation
Patent Information
- Application Number
- CN202410098582.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-24
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2044-01-24
AI Technical Summary
但是这种做法只能降低磕白出现的几率,并不能从根本上解决磕白现象
[0021]本发明将质量比例0.5-2.5%左右的微胶囊添加到聚丙烯材料中,微胶囊的壳体材料为二氧化硅,芯材为苯基甲基硅油或苯基乙烯基硅油或其他符合要求的油状物,聚丙烯材料的折光率在1.5左右,所选油状物的折光率也在1.5左右,二者接近,另外所选油状物的化学性质稳定,耐热性能好,将其添加到聚丙烯材料中,对电池的性能没有不良影响。普通双螺杆挤出机的加工间隙为0.5mm左右,本发明制备的微胶囊的尺寸不超过300μm,并且壳体材料二氧化硅有一定的强度,因此在加工过程中不会破裂,从而被均匀分散在树脂基体中。改性材料在外力作用下发生微裂纹时,该部位的微胶囊也同时发生破裂,其中的油状物芯材会扩散填充到树脂中的细微裂缝中,由于所选油状物与聚丙烯树脂的折光率接近,因此该部位的光散射程度会降低,使得电池壳体表面的磕白现象不明显。
Smart Images

Figure HDA0004679399480000011 
Figure HDA0004679399480000012 
Figure HDA0004679399480000013
Abstract
Description
Technical Field
[0001] This invention belongs to the field of storage batteries, and specifically relates to a modified polypropylene material for storage battery casings. Background Technology
[0002] Lead-acid batteries typically use copolymer polypropylene for their casings. These casings are often thin-walled, and the natural color of the copolymer polypropylene gives them a semi-transparent appearance. During manufacturing or handling, the casing may be subjected to impacts, resulting in extremely fine cracks (invisible to the naked eye) at the impacted areas. This causes light scattering, manifesting as a whitening effect. This is very noticeable against the backdrop of the electrolyte inside the battery, affecting its appearance and failing to meet casing aesthetic requirements, making it easily perceived as a defective product by customers. There is no effective solution to this whitening problem in the industry. The common practice is to add cushioning pads to the moving parts of the processing equipment that come into contact with the battery. However, this only reduces the probability of whitening and does not fundamentally solve the problem. Summary of the Invention
[0003] The purpose of this invention is to overcome the above-mentioned shortcomings of the prior art and provide a modified polypropylene material for battery casing, which effectively reduces the impact of chipping on the appearance of the battery.
[0004] The inventors discovered two main reasons for the whitening effect caused by impact: 1. Tiny cracks appear in the material after impact, causing light scattering and resulting in a whitening appearance; 2. The material is semi-transparent, and the whitening becomes more noticeable when the tank is filled with electrolyte. Addressing this issue through material modification can tackle both causes directly, fundamentally resolving the whitening problem. Regarding the first point, if an oily substance with a refractive index similar to polypropylene fills the cracks, light scattering in that area will be reduced, making the whitening less noticeable. Regarding the second point, adding inorganic pigments and fillers to the material reduces its translucency, making the translucency of the whitened area similar to that of the normal area, thus minimizing the whitening effect. These two approaches reduce the impact of whitening on appearance, fundamentally solving the problem.
[0005] The technical solution adopted in this invention is as follows: A modified polypropylene material for battery casing, the formulation of which includes the following raw materials in parts by weight: 93.7-98.1 parts of polypropylene resin, 0.3-0.8 parts of diffusion oil, 0.5-2 parts titanium dioxide, Microcapsules, 0.5-2.5 parts, Antioxidant 0.3-0.5 parts, 0.3-0.5 parts lubricant; The shell material of the microcapsules is silicon dioxide, and the core material is silicone oil; The microcapsules have a particle size of ≤300μm.
[0006] Preferably, the formulation comprises the following raw materials in parts by weight: 95.0-96.84 parts of polypropylene resin, 0.45-0.8 parts of diffusion oil, Titanium dioxide 0.95-2 parts, Microcapsules, 0.95-2.5 parts. Antioxidant 0.33-0.49 parts, Lubricant 0.33-0.49 parts.
[0007] The refractive index of the silicone oil is the same as that of the polypropylene resin.
[0008] The polypropylene resin is a copolymer polypropylene resin (typical grades include Yanshan Petrochemical K8003, Dushanzi Petrochemical EPS30R, ExxonMobil 7032KN, etc.).
[0009] The diffusion oil is a mineral oil (typically grade 10# white mineral oil, German VK AK-1000, etc.).
[0010] The titanium dioxide is commercially available rutile titanium dioxide with a mesh size of 2400-5000 mesh.
[0011] The lubricant is ethylene bis-stearamide with a mesh size of 325-500 mesh.
[0012] The antioxidant is obtained by compounding a primary antioxidant and an auxiliary antioxidant, with the ratio of the antioxidant to the auxiliary antioxidant being 1:1.8-2.2 and mixed evenly.
[0013] The primary antioxidant is antioxidant 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]); the secondary antioxidant is antioxidant 168 (phosphite).
[0014] A method for preparing the above-mentioned modified polypropylene material for battery casing includes the following steps: Weigh out the polypropylene resin and diffusion oil according to the formula, and stir for 1-2 minutes to mix the diffusion oil and polypropylene resin evenly to obtain polypropylene mixed with diffusion oil. Weigh out titanium dioxide, microcapsules, antioxidants, and lubricants according to the formula and add them to the polypropylene mixed with diffusion oil. Stir for 1-2 minutes to mix the components evenly, and the powder will adhere to the surface of the polypropylene particles to form a blend. The above blend is fed into a twin-screw extruder. The temperature range is 200-220℃, the screw speed is 350±10rpm, the feeding frequency is 10±1Hz, the vacuum degree is -0.1±0.01MPa, the extruded strip is rinsed with water, air-dried, and then pelletized to obtain the anti-whitening modified polypropylene material.
[0015] A microcapsule used in the above-mentioned modified polypropylene material includes a core material and an outer shell; the shell is silica; the core material is silicone oil; and the refractive index of the silicone oil is 1.50±0.1.
[0016] The silicone oil is phenylmethyl silicone oil or phenylvinyl silicone oil, or other oily substances with a refractive index of around 1.50.
[0017] A method for preparing the above-mentioned microcapsules includes the following steps: Step 1: Add a surfactant to the silicone oil, with the surfactant to silicone oil weight ratio being 5%-10%; the silicone oil is phenylmethyl silicone oil or phenyl vinyl silicone oil; mix the above silicone oil mixture with surfactant and deionized water at a weight ratio of 1:12.5-15, and stir the mixture at 60±5℃ and 600±50rpm for 20±5 minutes to form a stable oil-in-water emulsion; Step 2: Weigh an appropriate amount of sodium silicate and add an equal mass of deionized water to prepare a sodium silicate solution. At a speed of 600±50 rpm, add 1±0.05 mol / L hydrochloric acid solution dropwise to adjust the pH of the solution to 3±0.2, so as to form a transparent silicate precursor solution. Continue stirring for 30±5 minutes until it stabilizes. Step 3: Slowly add the silica precursor solution obtained in Step 2 to the oil-in-water emulsion of the same mass as the silica precursor solution, maintain 60±5℃, and stir at 600±50 rpm for 24±0.5 hours; then turn off the stirring, maintain the temperature at 60±5℃, and continue to stand for 5±0.5 hours to allow the silica precursor to complete the condensation reaction on the surface of the silicone oil to form a silica shell, thus obtaining a suspension of microcapsules with silica as the shell and silicone oil as the core material. Step 4: Let the obtained suspension stand, separate the liquids, rinse with deionized water and filter to obtain a white product. Dry the product at 60±5℃ for 5±0.5 hours to obtain the microcapsules.
[0018] The surfactant is obtained by compounding dodecylphenol polyoxyethylene ether and hexadecyltrimethylammonium bromide, with the compounding ratio of dodecylphenol polyoxyethylene ether to hexadecyltrimethylammonium bromide being 1:1-1.5.
[0019] This invention reduces the light transmittance of a material by adding a certain amount of titanium dioxide without altering its appearance. It also incorporates microcapsules containing an oily substance with a refractive index similar to that of polypropylene. When the capsule is impacted, the microcapsules rupture, releasing the oily substance to fill tiny cracks. This method reduces light scattering in these areas, thereby mitigating the impact of impact damage.
[0020] Natural polypropylene materials are generally white. Adding about 0.5-2% titanium dioxide to polypropylene materials does not significantly change their color. However, because titanium dioxide has a strong hiding power and also alters the crystallization of polypropylene, the combined effect of these two factors significantly reduces the light transmittance of the polypropylene shell, thus mitigating the whitening effect.
[0021] This invention adds microcapsules at a mass ratio of approximately 0.5-2.5% to polypropylene material. The shell material of the microcapsules is silica, and the core material is phenylmethyl silicone oil, phenyl vinyl silicone oil, or other suitable oily substances. The refractive index of the polypropylene material is approximately 1.5, and the refractive index of the selected oily substance is also approximately 1.5, which is close. Furthermore, the selected oily substance has stable chemical properties and good heat resistance, so its addition to the polypropylene material has no adverse effect on battery performance. The processing gap of a conventional twin-screw extruder is approximately 0.5 mm. The size of the microcapsules prepared by this invention does not exceed 300 μm, and the silica shell material has a certain strength, so it will not break during processing and is thus uniformly dispersed in the resin matrix. When the modified material develops microcracks under external force, the microcapsules in that area also rupture simultaneously. The oily core material diffuses and fills the tiny cracks in the resin. Because the refractive index of the selected oily substance is close to that of the polypropylene resin, the light scattering in that area is reduced, making the whitening phenomenon on the battery casing surface less noticeable. Attached Figure Description
[0022] Figure 1 This is a diagram of the pre-impact state of the injection molding tank of the anti-blow white modified polypropylene material in Embodiment 1 of the present invention.
[0023] Figure 2 This is a diagram showing the state of the injection molding tank of the anti-blow white modified polypropylene material in Embodiment 2 of the present invention before impact.
[0024] Figure 3 This is a diagram of the pre-impact state of the injection molding tank of the anti-blow white modified polypropylene material in Embodiment 3 of the present invention.
[0025] Figure 4 The diagram shows the state of the injection molding tank before impact after adding titanium dioxide to a common resin material for comparison.
[0026] Figure 5This is a diagram of the state of the injection molding tank of ordinary resin material before impact, as shown in Comparative Example 2.
[0027] Figure 6 This is a diagram showing the effect of the anti-blow white modified polypropylene material injection molding tank after impact in Embodiment 1 of the present invention.
[0028] Figure 7 This is a diagram showing the effect of the anti-blow white modified polypropylene material injection molding tank after impact in Embodiment 2 of the present invention.
[0029] Figure 8 This is a diagram showing the effect of the anti-blow white modified polypropylene material injection molding tank after impact in Embodiment 3 of the present invention.
[0030] Figure 9 This is a comparison of the impact effect on the injection molding tank of ordinary resin material in Example 2.
[0031] Figure 10 The effect of impact on the injection molding tank of polypropylene material is shown in Comparative Example 1. Detailed Implementation
[0032] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The following description of at least one exemplary embodiment is merely illustrative and is in no way intended to limit the present invention or its application or use. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0033] Techniques, methods, and equipment known to those skilled in the art may not be discussed in detail, but where appropriate, such techniques, methods, and equipment should be considered part of the specification. Example 1
[0034] Microcapsules were synthesized using silica as the shell and phenyl vinyl silicone oil as the core material via a sol-gel method. The synthesis method of the microcapsules is as follows: Step 1: Dodecylphenol polyoxyethylene ether and hexadecyltrimethylammonium bromide are compounded in a weight ratio of 2:3, stirred evenly, and then added to phenyl vinyl silicone oil at a mass fraction of 5%. The above phenyl vinyl silicone oil mixed with surfactant is mixed with deionized water in a weight ratio of 1:15 to obtain a mixture. The mixture is stirred at 60°C and 600 rpm for 20 minutes to form a stable oil-in-water emulsion. Step 2: Weigh an appropriate amount of sodium silicate and add the same amount of deionized water to prepare a sodium silicate solution. Add 1 mol / L hydrochloric acid solution dropwise to the solution at 600 rpm to adjust the pH value of the solution to 3, so as to form a transparent silicic acid precursor. Continue stirring for 30 minutes until it stabilizes. Step 3: Slowly add the silica precursor solution dropwise to the oil-in-water emulsion at a weight ratio of 1:1, maintain 60°C, and stir at 600 rpm for 24 hours; then turn off the stirring, maintain the temperature at 60°C, and continue to let it stand for 5 hours to allow the silica precursor to complete the polycondensation reaction on the surface of phenyl vinyl silicone oil to generate a silica shell. Step 4: Let the obtained microcapsule suspension stand, separate the contents, rinse with deionized water and filter to obtain a white product, then dry it at 60°C for 5 hours for later use.
[0035] Weigh 10 kg of polypropylene resin (commercially available copolymer polypropylene, typical grade K8003), then weigh 50 g of diffusion oil and stir for 2 minutes to mix the diffusion oil and polypropylene evenly. Weigh 100 g of titanium dioxide, 100 g of the self-made microcapsules, 36 g of antioxidant (1010:168=1:2), and 36 g of lubricant and add them to the polypropylene mixed with diffusion oil. Stir for 2 minutes to mix the components evenly and make the powder adhere to the surface of the polypropylene particles. Feed the above blend into a twin-screw extruder. At a temperature range of 200-220°C, a screw speed of 350 rpm, a feeding frequency of 10 Hz, and a vacuum degree of -0.1 MPa, the extruded strip is rinsed with water, air-dried, and then granulated to obtain the anti-whitening modified polypropylene material.
[0036] The injection molding tank made of anti-cracking white modified polypropylene material from Example 1, such as... Figure 1 As shown. Example 2
[0037] Microcapsules were synthesized using silica as the shell and phenylmethyl silicone oil as the core material via a sol-gel method. The synthesis method of the microcapsules is as follows: Step 1: Dodecylphenol polyoxyethylene ether and hexadecyltrimethylammonium bromide are compounded in a weight ratio of 1:1, stirred evenly, and then added to phenylmethyl silicone oil at a mass fraction of 10%. The above-mentioned phenylmethyl silicone oil mixed with surfactant is mixed with deionized water in a weight ratio of 2:25 to obtain a mixture. The mixture is stirred at 60°C and 600 rpm for 20 minutes to form a stable oil-in-water emulsion. Step 2: Weigh an appropriate amount of sodium silicate and add the same amount of deionized water to prepare a sodium silicate solution. Add 1 mol / L hydrochloric acid solution dropwise to the solution at 600 rpm to adjust the pH value of the solution to 3, so as to form a transparent silicic acid precursor. Continue stirring for 30 minutes until it stabilizes. Step 3: Slowly add the silica precursor solution dropwise to the water-oil emulsion at a weight ratio of 1:2, maintain 60°C, and stir at 600 rpm for 24 hours; then turn off the stirring, maintain the temperature at 60°C, and continue to let it stand for 5 hours to allow the silica precursor to complete the polycondensation reaction on the surface of phenylmethyl silicone oil to generate a silica shell. Step 4: Let the obtained microcapsule suspension stand, separate the contents, rinse with deionized water and filter to obtain a white product, then dry it at 60°C for 5 hours for later use.
[0038] Weigh 10 kg of polypropylene resin (commercially available copolymer polypropylene, typical grade EPS30R), then weigh 80 g of white mineral oil and stir for 2 minutes to mix the white mineral oil and polypropylene evenly. Weigh 200 g of titanium dioxide, 250 g of the self-made microcapsules, 36 g of antioxidant (1010:168=1:2), and 36 g of lubricant and add them to the polypropylene mixed with diffusion oil. Stir for 2 minutes to mix the components evenly and make the powder adhere to the surface of the polypropylene particles. Feed the above blend into a twin-screw extruder. At a temperature range of 200-220°C, a screw speed of 350 rpm, a feeding frequency of 10 Hz, and a vacuum degree of -0.1 MPa, the extruded strip is rinsed with water, air-dried, and then granulated to obtain the anti-cracking white modified polypropylene material.
[0039] The injection molding tank made of anti-collision white modified polypropylene material from Example 2, such as... Figure 2 As shown. Example 3
[0040] Microcapsules were synthesized using silica as the shell and phenyl vinyl silicone oil as the core material via a sol-gel method. The synthesis method of the microcapsules is as follows: Step 1: Dodecylphenol polyoxyethylene ether and hexadecyltrimethylammonium bromide are compounded in a weight ratio of 1:1, stirred evenly, and then added to phenyl vinyl silicone oil at a mass fraction of 8%. The above phenyl vinyl silicone oil mixed with surfactant is mixed with deionized water in a weight ratio of 1:15 to obtain a mixture. The mixture is stirred at 60°C and 600 rpm for 20 minutes to form a stable oil-in-water emulsion. Step 2: Weigh an appropriate amount of sodium silicate and add the same amount of deionized water to prepare a sodium silicate solution. Add 1 mol / L hydrochloric acid solution dropwise to the solution at 600 rpm to adjust the pH value of the solution to 3, so as to form a transparent silicic acid precursor. Continue stirring for 30 minutes until it stabilizes. Step 3: Slowly add the silica precursor solution dropwise to the water-oil emulsion at a weight ratio of 2:3, maintain 60°C, and stir at 600 rpm for 24 hours; then turn off the stirring, maintain the temperature at 60°C, and continue to let it stand for 5 hours to allow the silica precursor to complete the polycondensation reaction on the surface of phenyl vinyl silicone oil to generate a silica shell. Step 4: Let the obtained microcapsule suspension stand, separate the contents, rinse with deionized water and filter to obtain a white product, then dry it at 60°C for 5 hours for later use.
[0041] Weigh 10 kg of polypropylene resin (commercially available copolymer polypropylene, typical grade EPS30R), then weigh 80 g of diffusion oil and stir for 2 minutes to mix the diffusion oil and polypropylene evenly. Weigh 150 g of titanium dioxide, 200 g of the self-made microcapsules, 50 g of antioxidant (1010:168=1:2), and 50 g of lubricant and add them to the polypropylene mixed with diffusion oil. Stir for 2 minutes to mix the components evenly and make the powder adhere to the surface of the polypropylene particles. Feed the above blend into a twin-screw extruder. At a temperature range of 200-220℃, a screw speed of 350 rpm, a feeding frequency of 10 Hz, and a vacuum degree of -0.1 MPa, the extruded strip is rinsed with water, air-dried, and then granulated to obtain the anti-whitening modified polypropylene material.
[0042] The injection molding tank made of anti-collision white modified polypropylene material as described in Example 3 Figure 3 As shown.
[0043] Comparative Example 1 (Ordinary resin material with added titanium dioxide) Weigh 10 kg of polypropylene resin (commercially available copolymer polypropylene, typical grade EPS30R), then weigh 80 g of diffusion oil and stir for 2 minutes to mix the diffusion oil and polypropylene evenly. Weigh 150 g of titanium dioxide, 50 g of antioxidant (1010:168=1:2), and 50 g of lubricant and add them to the polypropylene mixed with diffusion oil. Stir for 2 minutes to mix the components evenly and make the powder adhere to the surface of the polypropylene particles. Feed the above blend into a twin-screw extruder. At a temperature range of 200-220℃, a screw speed of 350 rpm, a feeding frequency of 10 Hz, and a vacuum degree of -0.1 MPa, the extruded strip is rinsed with water, air-dried, and then granulated to obtain the polypropylene material.
[0044] Comparative Example 1: Injection Molding Tank Made of Polypropylene Material Figure 4 As shown.
[0045] Comparative Example 2 (Ordinary Resin Material) Weigh 10 kg of polypropylene resin (commercially available copolymer polypropylene, typical grade EPS30R), then weigh 80 g of diffusion oil and stir for 2 minutes to mix the diffusion oil and polypropylene evenly. Weigh 50 g of antioxidant (1010:168=1:2) and 50 g of lubricant and add them to the polypropylene mixed with diffusion oil. Stir for 2 minutes to mix the components evenly and make the powder adhere to the surface of the polypropylene particles. Feed the above blend into a twin-screw extruder. At a temperature range of 200-220℃, a screw speed of 350 rpm, a feeding frequency of 10 Hz, and a vacuum degree of -0.1 MPa, the extruded strip is rinsed with water, air-dried, and then granulated to obtain the polypropylene material.
[0046] The injection molding tank made of comparative dipropylene material, such as Figure 5 As shown.
[0047] Battery cells injection molded with the anti-whitening modified polypropylene material of Examples 1-3 were compared with those injection molded with Comparative Example 1 (polypropylene material with only added titanium dioxide) and Comparative Example 2 (ordinary polypropylene material). A 500g steel ball was dropped from a height of 55cm onto similar locations on the sides of the three battery cells. The battery cell injection molded with the anti-whitening modified material showed significantly less whitening on its surface than those injection molded with the other two materials. This demonstrates that the anti-whitening modified polypropylene material prepared in this invention has excellent anti-whitening effect. The impact effects of the three materials after injection molding are as follows: Figure 5-10 As shown.
[0048] The above description is merely an exemplary embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A modified polypropylene material for battery casing, characterized in that: Its formula includes the following ingredients in parts by weight: 93.7-98.1 parts of polypropylene resin, 0.3-0.8 parts of diffusion oil, 0.5-2 parts titanium dioxide, Microcapsules, 0.5-2.5 parts, Antioxidant 0.3-0.5 parts, 0.3-0.5 parts lubricant; The microcapsules have a particle size ≤300μm; The shell material of the microcapsules is silicon dioxide, and the core material is silicone oil; The refractive index of the silicone oil is the same as that of the polypropylene resin.
2. The modified polypropylene material for battery casing according to claim 1, characterized in that: Its formula includes the following ingredients in parts by weight: 95.0-96.84 parts of polypropylene resin 0.45-0.8 parts of diffusion oil, Titanium dioxide 0.95-2 parts, Microcapsules, 0.95-2.5 parts. Antioxidant 0.33-0.49 parts, Lubricant 0.33-0.49 parts.
3. The modified polypropylene material for battery casing according to claim 1, characterized in that: The polypropylene resin is a copolymer polypropylene resin; the diffusion oil is mineral oil; the titanium dioxide is commercially available rutile titanium dioxide with a mesh size of 2400-5000 mesh; the lubricant is ethylene bis-stearamide with a mesh size of 325-500 mesh; the antioxidant is obtained by compounding a primary antioxidant and an auxiliary antioxidant, with a compounding ratio of 1:1.8-2.
2.
4. The modified polypropylene material for battery casing according to claim 3, characterized in that: The primary antioxidant is antioxidant 1010; the secondary antioxidant is antioxidant 168.
5. A method for preparing a modified polypropylene material for a battery casing according to any one of claims 1-4, characterized in that: Includes the following steps: Weigh out the polypropylene resin and diffusion oil according to the formula, and stir for 1-2 minutes to mix the diffusion oil and polypropylene resin evenly to obtain polypropylene mixed with diffusion oil. Weigh out titanium dioxide, microcapsules, antioxidants, and lubricants according to the formula and add them to the polypropylene mixed with diffusion oil. Stir for 1-2 minutes to mix the components evenly, and the powder will adhere to the surface of the polypropylene particles to form a blend. The above blend is fed into a twin-screw extruder. The temperature range is 200-220℃, the screw speed is 350±10rpm, the feeding frequency is 10±1Hz, the vacuum degree is -0.1±0.01MPa, the extruded strip is rinsed with water, air-dried, and then pelletized to obtain the anti-whitening modified polypropylene material.
6. The application of a microcapsule in the modified polypropylene material according to any one of claims 1-4, characterized in that: The microcapsule comprises a core material and an outer shell; the shell is silicon dioxide; the core material is silicone oil; the refractive index of the silicone oil is 1.50±0.1; and the particle size of the microcapsule is ≤300μm.
7. The application of the microcapsules according to claim 6 in the modified polypropylene material according to any one of claims 1-4, characterized in that: The silicone oil is phenylmethyl silicone oil or phenylvinyl silicone oil.
8. A method for preparing microcapsules in the application described in claim 6 or 7, characterized in that: Includes the following steps: Step 1: Add a surfactant to the silicone oil, with the surfactant to silicone oil weight ratio being 5%-10%; the silicone oil is phenylmethyl silicone oil or phenyl vinyl silicone oil; mix the above silicone oil mixture with surfactant and deionized water at a weight ratio of 1:12.5-15, and stir the mixture at 60±5℃ and 600±50rpm for 20±5 minutes to form a stable oil-in-water emulsion; Step 2: Weigh an appropriate amount of sodium silicate and add an equal mass of deionized water to prepare a sodium silicate solution. At a speed of 600±50 rpm, add 1±0.05 mol / L hydrochloric acid solution dropwise to adjust the pH of the solution to 3±0.2, so as to form a transparent silicate precursor solution. Continue stirring for 30±5 minutes until it stabilizes. Step 3: Slowly add the silica precursor solution obtained in Step 2 to the oil-in-water emulsion of the same mass as the silica precursor solution, maintain 60±5℃, and stir at 600±50 rpm for 24±0.5 hours; then turn off the stirring, maintain the temperature at 60±5℃, and continue to stand for 5±0.5 hours to allow the silica precursor to complete the condensation reaction on the surface of the silicone oil to form a silica shell, thus obtaining a suspension of microcapsules with silica as the shell and silicone oil as the core material. Step 4: Let the obtained suspension stand, separate the liquids, rinse with deionized water and filter to obtain a white product. Dry the product at 60±5℃ for 5±0.5 hours to obtain the microcapsules.
9. The method for preparing microcapsules according to claim 8, characterized in that: The surfactant is obtained by compounding dodecylphenol polyoxyethylene ether and hexadecyltrimethylammonium bromide, with the compounding ratio of dodecylphenol polyoxyethylene ether to hexadecyltrimethylammonium bromide being 1:1-1.5.
Citation Information
Patent Citations
Silicone oil microcapsule with slow-release characteristics and preparation method thereof
CN102030990A